Associations of LPL and APOC3 gene polymorphisms on plasma lipids in a Mediterranean population: interaction with tobacco smoking and the APOE locus - Dolores Corella; Marisa Guillén; Carmen Sáiz; Olga Portolés; Antonio Sabater; José Folch; Jose M. Ordovas (Journal of Lipid Research, 2002)
We conducted a cross-sectional study in a Spanish population (n = 1,029) to investigate associations between the LPL and APOC3 gene loci (LPL-HindIII, LPL-S447X, and APOC3-SstI) and plasma lipid levels and their interaction with APOE polymorphisms and smoking. Carriers of the H− or the X447 allele had higher levels of HDL cholesterol (HDL-C), and lower levels of TG, after adjustment for age, body mass index, alcohol, smoking, exercise, and education (P < 0.01). The APOC3 polymorphism presented additive effects to the LPL variants on TG and HDL-C levels in men, and on TG in women. The most and the least favorable haplotype combinations were H−/X447/S1 and H+/S447/S2, respectively. These combinations accounted for 7% and 5% of the variation in HDL-C and TG in men, and 3% and 4% in women. There was a significant interaction between APOE and LPL variants and HDL-C levels in both genders (P < 0.05). The increases in HDL-C observed for the rare alleles were higher in ε4 than in ε3 subjects, and absent in ε2 individuals. This effect was modulated by smoking (interaction HindIII-APOE-smoking, P = 0.019), indicating that smoking abolished the increase in HDL-C levels observed in ε4/H− subjects. Understanding this gene-gene-environmental interaction may facilitate preventive interventions to reduce coronary artery disease risk. —Corella, D., M. Guillén, C. Sáiz, O. Portolés, A. Sabater, J. Folch, and J. M. Ordovas. Associations of LPL and APOC3 gene polymorphisms on plasma lipids in a Mediterranean population: interaction with tobacco smoking and the APOE locus.